The Sunflower Forest (A novel) - Hayden, Torey (London HarperCollins Publishers, 2008)
Bestselling author Torey Hayden's new novel poignantly tells of a daughter's attempt to grow up in the shadow of her mother's haunted past. Warm, melancholy and evocatively rendered this book captures the essence of a family touched by sadness.
Keywords: Germany -- Eugenics -- Mothers and daughters